Research methods for leisure, recreation and tourism - Sirakaya-Turk, Ercan, ....-; Uysal, Muzaffer S., ....- (Wallingford : CABI, 2017)
Describing the fundamental elements of research methods for leisure, recreation and tourism, this new edition of a popular textbook is updated throughout. It covers the measurement of variables, sampling, questionnaire design and evaluation methods, and also a wider discussion of writing proposals, communicating research findings, cross-cultural research, and the use of new technologies in conducting research.
Includes bibliographical references and index.
Keywords: Leisure -- Research -- Methodology; Recreation -- Research -- Methodology; Tourism -- Research -- Methodology